Synthesis and structure of novel lithium-ion conductor Li7Ge3PS12 - Inoue, Yuki; Suzuki, Kota; Matsui, Naoki; Hirayama, Masaaki; Kanno, Ryoji (Journal of solid state chemistry, 2017)
The novel lithium-ion conductor Li7Ge3PS12 was synthesized by slow cooling from the ternary Li2S–GeS2–P2S5 system, and was shown to exhibit a cubic argyrodite-type structure. The phase composition was determined by varying the ratio of starting materials; the observed monophasic properties were close to those for the Li7Ge3PS12 composition. The lattice parameter (a =9.80192(3) Å) of Li7Ge3PS12 was slightly smaller than that of Li7PS6 (a =9.993Å), indicating that substitution of a Li cation by the smaller Ge cation contracted the cubic lattice. In addition, the novel structure consisted of a framework composed of four isolated (Ge/P)S4 tetrahedra. Li+ ions occupied tetrahedral sites within the framework, forming a three-dimensional conduction pathway. Finally, Li7Ge3PS12 exhibited a high ionic conductivity of 1.1×10−4 S cm−1 at 25°C and an activation energy of 25kJmol−1. A novel Li7Ge3PS12 solid lithium ion conductor, with cubic argyrodite strucuture, shows high ion conductivity of 1.1×10–4 S cm–1 with an activation energy of 25kJmol–1. The argyrodite structure consists of (Ge/P)S4 tetrahedra units along with partial occupation of lithium and germanium at 48h site. [Display omitted] •A novel lithium-ion conductor Li7Ge3PS12 was detected.•This was achieved through slow cooling of the ternary Li2S–GeS2–P2S5 system.•This novel conductor revealed a cubic argyrodite-type structure.•Li7Ge3PS12 exhibited a high ionic conductivity of 1.1×10−4 S cm−1 at 25°C.•These properties will aid in the design of superior lithium-ion conductors.